Hogar de ancianos Ben Sion Bouer (2003)
Construido en el barrio de Las Flores, Bs.As.
Keywords: ARGENTINA; BUENOS AIRES; VIVIENDAS PARA ADULTOS MAYORES; RESIDENCIAS PARA ADULTOS MAYORES; FLAH, RAIMUNDO; BOUNAMASSA, STELLA; BRUSCO, LUIS RODOLFO